Which Risks Get Managed? Addressing Climate Effects in the Context of Evolving Water-Governance Institutions - Ken Conca (Water Alternatives, 2015)
Warnings about climate change invariably stress water-related effects. Such effects are typically framed as both unpredictable and disruptive, and are thus said to create large new risks to the water sector demanding adaptive responses. This article examines how such responses are mediated by, and also compromised by, two dominant trends in the evolution of water governance institutions: (1) the rise of an “integrated” paradigm of water resources management, which has encouraged the development of more complex and interconnected water institutions, and (2) the rapidly changing political economy of water financing and investment. Each of these trends carries its own strong presumptions about what constitutes water-related risk and how such risk is properly managed. The article uses the specific example of large dam projects to illustrate how these ongoing trends in water governance shape and complicate the prospect of managing climate-water risks.